Documentation practices in agile 5G network projects - Alkwai, Lamia; Almansour, Ibrahem; Alhazmi, Hatim (Frontiers in Communications and Networks, 2025)
The deployment of a private 5G network using srsRAN involves complex and iterative processes that benefit from agile project management practices. Agile methodologies, characterized by iterative development, flexibility, and continuous feedback, can greatly enhance the efficiency and effectiveness of such projects. However, these practices also pose unique challenges for documentation. Effective documentation is crucial in agile projects, as it ensures that all stakeholders are aligned and that knowledge is preserved throughout the development lifecycle. In the context of 5G network projects, where technical complexity and evolving requirements are prevalent, documentation must balance thoroughness with agility. It must be comprehensive enough to support technical development and integration but flexible enough to accommodate changes and updates as the project progresses. This paper explores the documentation practices employed in agile 5G network projects, specifically focusing on the experience of deploying a private 5G network using srsRAN. By examining the documentation approaches used in this context, we aim to identify best practices and propose improvements that can enhance project management and outcome. The insights gained from this research are intended to contribute to a better understanding of how documentation can be optimized in agile frameworks to support the successful deployment of private 5G networks.